Criticism and analysis of the book "Fundamentals of the Islamic Republic of Iran's constitutional Law" - Ebrahim Mousazadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The importance of this criticism is due to the status of the constitutional law, the constitution and the rule of the Islamic Republic, and the necessity of criticism is also the motivation for the formation of the effect of criticism as a teaching resource for the constitutional law course in law and subjects related to constitutional law in postgraduate courses in the field of public law. The purpose of this critique is to identify the strengths and weaknesses of the work as "academic books" and to modify the proposed issues and to eliminate existing shortcomings. The method of critique is citation-analytical methodology, and legal logic-based analysis of the legal knowledge is critical in the overall context of a critique of form, and content review. It also assesses the quantity and quality of resources, references, and citations. The results indicate that this critique in terms of methodology and coordination of content, objectives and training needs and the cohesion and logical relationship between the components should be fundamentally revision. Also, due to the lack of balanced processing of the material, it is also subject to both theoretical and internal contradictions.